Machining Performance of Ti-6Al-4V Titanium Alloy Assisted by High Pressure Waterjet - Abu Bakar, Mohd Hadzley; Raja Abdullah, Raja Izamshah; Md. Ali, Mohd Amran; Jusoff, Kamaruzzaman; Sivarao, Subramonian; Ariff, Hambali; Hussein, Nur Izan Syahriah; Wan Mahmood, Wan Hassrulnizzam; Abdullah, Abu; Yusoff, Marianna; Shamshiri, Meysam (IDOSI Publications, 2013)
The High Pressure Waterjet Assisted Machining (HPWAM) is a machining process that involves high pressure coolant being delivered at the cutting zone. This paper investigates the performance of conventional and HPWAM when machining Ti-6Al-4V titanium alloy. The evaluations were based on the tool life, wear mechanisms, surface profile and chip formation. The coolant pressures, cutting speed, feed rate and depth of cut were set at 11-20.3 MPa, 110m/min, 0.15 mm/rev and 0.5 mm respectively. The results showed that improved tool life as much as 195% can be achieved when machining Ti-6Al-4V with HPWAM due to better coolant access at the cutting zone. Surfaces generated when machining with HPWAM were generally acceptable with negligible physical damage. Long and continuous chip formations were observed when machining in conventional coolant supply corresponded to the low coolant pressure. Increasing coolant pressure significantly reduces the chip size, resulting in a reduction in the tool-chip contact and improvement in lubrication at the contact interfaces. This paper provides the understanding and correct use of HPWAM especially when machining Ti-6Al-4V alloy.